Hate spin: the manufacture of religious offense and its threat to democracy - George, Cherian (Information policy series, 2016)
Hate spin as politics by other means -- By what rules? : human rights and religious authority -- God, Google, and the globalization of offendedness -- India : Narendra Modi and the harnessing of hate -- Indonesia : democracy tested amid rising intolerance -- United States : exceptional freedoms, fabricated fears -- Pushing back, through media and civil society -- Assertive pluralism for a world of irreducible diversity